Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s12687-017-0294-8
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary premarital screening to prevent sickle cell disease in Jamaica: does it work?

Abstract: To determine whether identifying haemoglobin genotype, and providing education and counselling to senior school students will influence their choice of partner and reduce the frequency of births with sickle cell disease. The Manchester Project provided free voluntary blood tests to determine haemoglobin genotype to the fifth and sixth forms (grades 11-13), median age of 16.7 years, of all 15 secondary schools in the parish of Manchester in south central Jamaica. A total of 16,636 students complied, and counsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…SCD is one of the most widespread monogenic diseases in the world, with over 300,000 babies born with SCD every year [4, 11]. It commonly affects many African and Asian countries, with the Middle East being one of the most prominently affected regions [1, 4, 1214].…”
Section: Introductionmentioning
confidence: 99%
“…SCD is one of the most widespread monogenic diseases in the world, with over 300,000 babies born with SCD every year [4, 11]. It commonly affects many African and Asian countries, with the Middle East being one of the most prominently affected regions [1, 4, 1214].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive program for bride and groom candidate previously is applied by developed countries. The government requires the bride and groom canditate to receive premarital education and reproductive and genetic health examination (Ibrahim et al, 2011, Serjeant et al, 2017.…”
Section: Resultsmentioning
confidence: 99%
“…This is in contrast with the reports of Uche [15] which reported that majority of students from families with an average income above N150,000 per year seem to have good awareness of SCD compared to students from families with lesser income. The disparity in the proportion of awareness among the students based on their socio-economic status could be attributed to either lack of interest and sometimes lack of adequate sources of information among the different socio-economic classes [17,22,23].…”
Section: Discussionmentioning
confidence: 99%